Development of Outdoor Bench for Recreational Park - Yusri, Muhammad Yusman Najmi; Sidek, Ahmad Anwar Safwan (Research in Management of Technology and Business, 2025)
Outdoor benches that are solid, durable, and have a lovely shape play an important role in public parks. As a result, benches are employed to brighten up parks. Many individuals, including the elderly and small children, rely on recreational parks to rest their feet after a stroll or other activity. The goals of this research were to determine the design criteria for outdoor benches as well as to design and develop a prototype acceptable for visitors at recreational park in Maran. A questionnaire was given using Microsoft Forms to 100 respondents in Maran, Pahang. According to the poll, the recommended design criteria for outdoor benches were wood as the main material, a backrest bench, no stagnant water problem, and high durability. Ideation, idea development, a design survey, the final design, and mock-up creation were all part of the design process. Each phase led to the improvement of outdoor bench to fulfil the design standards. The findings of this study can be used to guide future research and enhance the design of outdoor benches and achieve the objectives of Sustainable Development Goals (SDG).